16S rRNA Sequencing Reveals Relationship Between Potent Cellulolytic Genera and Feed Efficiency in the Rumen of Bulls - McGovern, Emily; Kenny, David A.; McCabe, Matthew S.; Fitzsimons, Claire; McGee, Mark; Kelly, Alan K.; Waters, Sinéad M. (Frontiers in Microbiology, 2018)
The rumen microbial population dictates the host’s feed degradation capacity and subsequent nutrient supply. The rising global human population and intensifying demand for animal protein is creating environmental challenges. As a consequence, there is an increasing requirement for livestock with enhanced nutrient utilisation capacity in order to more efficiently convert plant material to high quality edible muscle. In the current study, residual feed intake, a widely used and a highly accepted measure of feed efficiency in cattle, was calculated for a combination of three cohorts of Simmental bulls. All animals were managed similarly from birth and offered concentrate ad libitum in addition to 3kg of grass silage daily during the finishing period. Solid and liquid rumen digesta samples collected at slaughter and were analysed using amplicon sequencing targeting the 16S rRNA gene utilising the Illumina MiSeq platform. Volatile fatty acid analysis was also conducted on the liquid digesta samples. Spearman’s correlation coefficient was utilised to determine the association between RFI and bacterial and archaeal taxa and inter-taxonomic relationships. The data indicate a tendency towards an increase in butyrate (P=0.06) which corresponds with an increase in plasma β-hydroxybutyrate concentration in low RFI (LRFI) bulls in comparison to their high RFI (HRFI) contemporaries (P<0.05). A decrease in propionate (P<0.05) was also recorded in the rumen of LRFI in comparison to HRFI bulls. These results indicate alternate fermentation patterns in the rumen of LRFI bulls. The data also identified that OTUs within the phyla Tenericutes, Fibrobacteres and Cyanobacteria may potentially influence RFI phenotype. In particular, a negative association between F.succinogenes and RFI was evident. The unique cellulolytic metabolism of F.succinogenes suggests it could contribute to host efficiency by providing substrate to the host ruminant and other microbial populations (e.g. Selenomonas ruminantium, Methanobrevibacter and Methanomassiliicoccaceae) in the rumen. This study provides evidence that bacterial OTUs within common phyla could influence ruminant feed efficiency phenotype through their role in ruminal degradation of complex plant polysaccharides or increased capability to harvest nutrients from ingested feed.